A Case Of Pulmonary Tb Complicated With Fibrothorax Treated Successfully Via Intrapleural Fibrinolytic And Anti-Tuberculous Agents - Ng, CS; Ban, AYL; Soo, CI; Faisal, AH; Aziz, AM; Ummi, ND; Hassan, T; Roslina, AM (Wiley-Blackwell, 2024)
Indexed by WOS